ANALISIS NILAI TAMBAH PRODUK OLAHAN IKAN LELE OLEH UMKM MANG NCUN DI KOTA BANDUNG - Junianto Junianto; Atik Nur Latifah; Nabil Fathi Muyassar; Nevi Widyawati; Rizka Wachida Arhab (Fakultas Pertanian, Universitas Janabadra, 2024)
This study aims to analyze the added value of catfish processing at MSME Mang Ncun. This study was conducted in March 2024 in Ganjar Sabar Village, Nagreg District, Bandung Regency. The method used is a case study method with a purposive sampling method. The types of data used are primary data and secondary data. Primary data were obtained from interviews with business founders. Secondary data were obtained from the Bandung Regency Food and Fisheries Service, as well as literature studies related to this research. The data were analyzed descriptively quantitatively to measure the overall components of added value that could answer the research objectives. The analysis method used to calculate added value is the Hayami method. The research results show that the added value generated from processed catfish products creates an added value of IDR 178,000/kg, the ratio of added value to product value is 58%. This shows that the catfish processing business at MSME Mang Ncun in Nagreg District, Bandung Regency provides high added value.